The Clean Water Act in Maine: Goals and Financing - Fisk, Andrew (Maine Policy Review, 2008)
Andrew Fisk gives an overview of the history of the federal Clean Water Act and of Maine’s efforts to improve the quality of the state’s lakes, rivers and streams. He describes how the Clean Water Act works and how its provisions are implemented. While the quality of Maine’s water bodies has improved greatly, much work still remains to be done in the areas of rain and stormwater runoff and mercury pollution, and in having adequate financing and infrastructure over the long term.